Pengaruh Pengetahuan Multimedia Pembelajaran, Berpifikir Kritis terhadap Efektifitas Modul E-Learning Mahasiswa Fakultas Teknik UNM - Latif, Nurlaela; Romadin, Achmad; Hasyim, Muhammad (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study is an Ex Post Facto study because the independent variables are not manipulated or subjected to specific treatments; instead, they are analyzed based on symptoms that appeared in respondents before the study's initiation. Adopting a cause-and-effect approach of "if x then y," this study does not involve direct control over the independent variables. Three variables are examined: two independent variables, Multimedia and Critical Thinking, and one dependent variable, the Effectiveness of the e-module. The relationship between the variables is analyzed using the correlation method, while the module's effectiveness is assessed through a quasi-experiment involving four control classes and four experimental classes. The study's results indicate that: (1) Multimedia and Critical Thinking collectively influence the Effectiveness of the E-learning Module, (2) Multimedia has a significant individual effect, whereas Critical Thinking has only a minimal impact, and (3) the Paired Samples t-test reveals an increase in learning outcomes, with an average difference of -13.92 between the Pre-Test and Post-Test. The regression analysis yielded a value of 71.314, categorizing it as effective. This e-learning module has demonstrated considerable effectiveness in enhancing understanding related to Multimedia.